Examining belief-adjustment model and investors overconfidence on investment decision making - Dyah Eras Mita; Luciana Spica Almilia (University of Merdeka Malang, 2019)
This research aims to examine whether there is a different judgment between the investor who receives good news followed by bad news and the one who receives bad news followed by good news information order in the step-by-step and the end-of-sequence disclosure pattern by using financial information type and non-financial information type and overconfidence characteristics on investment decision making. This research is included in the experimental design by using a mixed design of between-subjects and within-subject design and classified as experimental research which uses the 2x2x2 method. Participants used in this research are undergraduate business students in STIE Perbanas Surabaya who are studying and/or have completed investment management and/or financial statement analysis courses who will serve as non-professional investors. The results obtained in this research showed that recency effect occurred between the investor who receives good news followed by bad news and the one who receives bad news followed by good news in the step by step disclosure pattern, while there is no order effect occurred when the disclosure pattern used is the end-of-sequence.JEL Classification: G02, G11, G17DOI: https://doi.org/10.26905/jkdp.v23i4.3203